Integration of gasification and solid oxide fuel cells (SOFCs) for combined heat and power (CHP) - Costa, Paula (2021)
ABSTRACT: This paper reviews the most recent information about the main operations to produce energy from carbonaceous materials, namely biomass and wastes through the integration of gasification, syngas cleaning and solid oxide fuel cells (SOFCs), which have shown to be a good option for combined heat and power (CHP) production, due to high efficiency and low environmental impact. However, some challenges still need to be overcome, mainly when mixed feedstocks with high contents of hazardous contaminants are used, thus syngas cleaning and conditioning is of major importance. Another drawback is SOFC operation, hence new materials especially for the anode has been proposed and tested. An overall process to produce CHP by gasification integration with SOFC is proposed.